2020
DOI: 10.1039/c9tb02198a
|View full text |Cite
|
Sign up to set email alerts
|

Dual ultrasound-activatable nanodroplets for highly-penetrative and efficient ovarian cancer theranostics

Abstract: Upon US irradiation, FA-H@NDs can be activated for ADV-augmented deep penetration of sonosensitizers and SDT-induced therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…SDT ( Figure 4A). [37] Under US irradiation, the produced ADV phenomenon was shown to disrupt the adjacent vasculature system to reduce the resistance of drug diffusion, enabling nanosensitizers to penetrate deeper into the inner tissue.…”
Section: Organic-small-molecule Sonosensitizersmentioning
confidence: 99%
See 3 more Smart Citations
“…SDT ( Figure 4A). [37] Under US irradiation, the produced ADV phenomenon was shown to disrupt the adjacent vasculature system to reduce the resistance of drug diffusion, enabling nanosensitizers to penetrate deeper into the inner tissue.…”
Section: Organic-small-molecule Sonosensitizersmentioning
confidence: 99%
“…[16] Induction of cell death in vitro and distinct suppression of tumor growth in vivo adequately demonstrated Reproduced with permission. [37] Copyright 2019, Royal Society of Chemistry. B) Schematic representation of EXO-DVDMS.…”
Section: Organic-small-molecule Sonosensitizersmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the unwanted side effect could also be decreased through encapsulation of chemotherapy. It has been reported that perfluoropentane (PFP) owns an outstanding capacity of transforming from liquid phase to gas phase under irradiation, which could be applied as a novel ultrasound molecular probe, especially in ultrasonic imaging and treatment [30]. More importantly, the initial liquid phase enables PFP to be readily encapsulated in various materials [31].…”
Section: Introductionmentioning
confidence: 99%